Assessment of the impact of symbiont Ophiostomatales (Fungi) on mountain pine beetle (Coleoptera: Curculionidae) performance on a jack pine (Pinaceae) diet using a novel in vitro rearing method. Issue 1 (15th June 2015) - Myrholm, Colin L.; Langor, David W.
Abstract: A novel "rearing-tube" method was developed and used to investigate the performance of mountain pine beetle (MPB), Dendroctonus ponderosae Hopkins (Coleoptera: Curculionidae: Scolytinae), with its three main ophiostomatalean fungal symbionts, Grosmannia clavigera (Robinson-Jeffrey and Davidson) Zipfel, de Beer, and Wingfield (Ophiostomataceae), Ophiostoma montium (Rumbold) von Arx (Ophiostomataceae), and Leptographium longiclavatum Lee, Kim, and Breuil (Ophiostomataceae). Transparent glass tubes filled with sterile ground jack pine ( Pinus banksiana Lambert; Pinaceae) phloem and sapwood (9:1 ratio) were used to rear MPB from egg to adult with each fungus under controlled environmental conditions. Mountain pine beetle mortality was higher and development longer in fungus-free controls compared to fungal treatments. Among fungal treatments, insects developed faster, constructed shorter larval galleries, and had fewer supernumerary instars with L. longiclavatum. Insect survival was not affected by fungal treatments. Hyphal extension through the rearing medium was fastest for L. longiclavatum . Phloem nitrogen was reduced significantly by the presence of L. longiclavatum. Results support the hypothesis that ophiostomatalean symbionts provide benefits to MPB. The rearing-tube method is useful to tease apart confounding interspecific interactions between bark beetles and symbiotic fungus species.